Estudo dos arranjos supramoleculares por difração de raios X e pela Teoria do Funcional da Densidade de duas Heteroaril-Chalconas e dois Derivados do Antraceno - Costa, Rogério Ferreira da (2021)
The structural knowledge of organic compounds obtained from techniques such as X-ray crystallography is of fundamental importance in the development of civilization, because from them we can understand their properties and applications. In this work the molecular structures of a pair of chalcones and anthracene were studied by Hirshfeld surface and Density Functional Theory. From the results obtained from the boundary molecular orbitals and from the Molecular Electrostatic Potential maps, it was possible to predict the chemical properties of both compounds. The supramolecular arrangements were also theoretically studied, through the analysis of Natural Bonding Orbitals and the Quantum Theory of Atoms in Molecules. The results for the chalcone molecules indicate that the interactions are of a purely electrostatic nature. The change in the positioning of the chlorine in the chalcone molecules alters the interaction sites; however, chlorine does not participate effectively in any of the interactions for the formation of these crystals. The study of anthacene derivates showed that compounds have electronically stable molecules and weakly complexed in the formation of their respective crystals, so that the donor orbitals and acceptor orbitals hyperconjugate with very low second-order energy. In addition, the electronic density in the regions where the interactions occur is of the closed-shell type.